The Making of Islamist-inspired Terrorism and It’s Counter-terrorism in Indonesia - Arrobi, Mohammad Zaki (Jurnal Politik Indonesia: Indonesian Political Science Review, 2018)
The study attempts to uncover the making of Islamist-inspired terrorism and its state-led counter-terrorism responses in the modern history of Indonesia. It argues that Islamist-inspired terrorism and its counter-terrorism have been inextricably linked in complex ways within political and historical contexts. Instead of regarding Islamist-inspired terrorism and counter-terrorism as separated and unrelated entities, or perceiving the latter as just response to the former, it suggests that they have been intertwined and shaped each other throughout Indonesia’s modern history. By discussing Islamist-inspired terrorism in the three Indonesian historical periods, namely the resurgence of Darul Islam during 1940-60s, the re-emergence of Darul Islam networks and its series of terrorist attacks in 1980s, and the Jemaah Islamiyah-related terrorist activities in the 2000s as illustrative cases, the study has delineated the ways in which Islamist-inspired terrorism and its state-led counter-terrorism have been bound up within particular political, historical, and sociological context. In addition to that, the study also reveals that both Islamist-inspired terrorism and its state-led counter-terrorism have been shaped by the dynamic interplay of local, national, and global contexts.